Produksi Film Pendek Fiksi Guna Meningkatkan Kedisiplinan Presensi Di Lingkup Dinas Kominfo Provinsi Papua Barat - Steffany, Gabriella Aurellia; Kurniawan, Ady Purna; Sularsa, Anang (eProceedings of Applied Science, 2024)
Realizing one's readiness to Follow all company policies and social norms what is relevant is the definition of discipline. Potential increasing an employee's work performance increases with the level of discipline. Film short is a narrative told through sound and visual and arranged using existing situations previous, camera play, and editing methods. The aim of making a short fiction film about Increasing Attendance Discipline in the Service Environment Communication and Informatics of West Papua Province is to provide information to the public especially employees about the importance of work discipline and attendance discipline. Short film research, synopsis, scenarios, talent selection, storyboards, and preparation production equipment is all part of production process. Keywords: Discipline, Short Film, Production Stage